Growth through heterogeneous innovations - Ufuk Akcigit; William R. Kerr (Bank of Finland, 2013)
We study how exploration versus exploitation innovations impact economic growth through a tractable endogenous growth framework that contains multiple innovation sizes, multi-product firms, and entry/exit. Firms invest in exploration R&D to acquire new product lines and exploitation R&D to improve their existing product lines. We model and show empirically that exploration R&D does not scale as strongly with firm size as exploitation R&D. The resulting framework conforms to many regularities regarding innovation and growth differences across the firm size distribution. We also incorporate patent citations into our theoretical framework. The framework generates a simple test using patent citations that indicates that entrants and small firms have relatively higher growth spillover effects.
URN:NBN:fi:bof-20140807340
Keywords: O31; O33; O41; L16; 330; Endogenous Growth; Innovation; Exploration; Exploitation; Research and Development; Patents; Citations; Scientists; Entrepreneurs